Interdisciplinarity and research - Gauer, Ruth M. Chittó (2014)
The article analyzes in a first step the theme of interdisciplinarity, focusing the issues of time and new technologies. On a second moment, the article analyzes the connections between the interdisciplinary spaces in the current form of organization of the university. Is the contemporary structure of the university, grown up on a specialization basis, able to conduct itself an unprecedented renovation guided by the interdisciplinary cooperation, detached from its traditional specialist premise?